(untitled) (Bangladesh Journal of Botany, 2021)
To evaluate the in vitro antifungal activity of five fungicides viz., Capvit 50 WP, Contaf 5 EC, Greengel 72 WP, Knowin 72 WP and Score 250 EC as well as five plant extracts viz., Acalypha indica L., Azadirachta indica A. Juss., Heliotropium indicum L., Lippia alba L. and Magnolia champaca L. at different concentrations were selected against Colletotrichum dematium and C. gloeosporioides following poisoned food technique. Among the five fungicides, Capvit 50 and Score 250 showed the complete growth inhibition of C. dematium whereas Contaf 5 EC showed the complete growth inhibition of C. gloeosporioides at all the concentrations. Contaf 5 was found as the most effective inhibitor against C. dematium. On the other hand, Knowin 72 and Score 250 were found as the most effective fungicides against C. gloeosporioides. A. indica and L. alba showed highest radial growth inhibition of C. dematium and C. gloeosporioides at 20% concentration. Moreover, A. indica and M. champaca also showed desired growth inhibition of the test pathogens. This study paves the way for the management of C. dematium and C. gloeosporioides causing anthracnose disease of chilli. Bangladesh J. Bot. 50(2): 437-440, 2021 (June)